Healthcare access for refugee women with limited literacy: layers of disadvantage - Annette Floyd; Dikaios Sakellariou (BMC, 2017)
Abstract Background Record numbers of people, across the world, are forced to be displaced because of conflict or other violations of their human rights, thus becoming refugees. Often, refugees not only have a higher burden of disease but also compromised access to healthcare, as they face many barriers, such as limited knowledge of the local language. However, there is very limited knowledge on the lived experiences of this population. Moreover, the strategies people might develop in their efforts to access healthcare have not been explored in depth, despite their value in establishing peer- support, community based programs. Methods In this article, we present the findings of a study aiming to explore the lived experiences of accessing healthcare in the greater Vancouver area for recently-arrived, government-assisted refugee women, who were non-literate and non-English-speaking when they arrived in the country. We carried out sixteen semi-structured interviews with eight refugee women, guided by descriptive phenomenology. Results The findings highlight the intersection of limited knowledge of the local language with low literacy, gender, and refugee status and how it impacts women's access to healthcare, leading to added layers of disadvantage. We discuss three themes: (1) Dependence, often leading to compromised choice and lack of autonomy, (2) Isolation, manifesting as fear in navigating the healthcare system, rejection, or shame for a perceived inadequacy, and (3) Resourcefulness in finding ways to access healthcare. Discussion We propose that a greater understanding of the intersections of gender, low literacy, and refugee status can guide healthcare workers and policy makers in improving services for this population. Furthermore, It is important to enable seldom-heard, hard to reach populations and facilitate their participation in research in order to understand how vectors of disadvantage intersect.